Pelatihan Trik Menciptakan Peluang Usaha Untuk Karyawan Bumnag Kenagarian Malay V Suku Timur - Yusnaena Yusnaena; Haryeni, Erdasti Husni, Deddi Julianto (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
The Nagari-owned business entity is renamed Malay V Eastern Tribe. based on the results of interviews in the field, it indicates that this business entity has not been productive at all, no business has been carried out. existing capital does not yet function to grow the economy of the community, even though based on historical data there are many fields of business that can be fostered, because this livelihood is a productive livelihood, but this does not correlate with enthusiasm in managing this rural business entity, the results of our interviews with Walinagari It seems that people are confused and have not found entrepreneurial activities like what they will do to produce this Alumni Department. Based on the above phenomena, our team will provide training and counseling to the Eastern Tribal Kenagarian Malay V community to provide knowledge on how to create an entrepreneur, which we pack in topic "Tricks for giving birth to Entrepreneurship" After this activity was held, BUMNAG was active and started its activities. The purpose of this activity is to activate the existence of the Nagari business entity in kenagarian and provide entrepreneurial knowledge for its members in order to be able to manage the existence of a nagari-owned business entity that they already have. This activity will be followed by the community and the management of the Kenagarian V Alumni Association in East Malay, as many as 15 people.